Best Proximity Point Theorems for Suzuki Type Proximal Contractive Multimaps: Jamnian Nantadilok, P. Sumati Kumari, Buraskorn Nuntadilok - Team, Support (Thai Journal of Mathematics, 2018)
The purpose of this manuscript is to establish new best proximity point results for Suzuki type proximal contractive multimaps. Our results extend some recent known results by Hussain et al.[9] as well as other results in the literature. An illustrative example is provided to highlight our main results.